Front Cover. Issue 10 (8th September 2020) - Pinkert, Stefan; Zeuss, Dirk; Dijkstra, Klaas‐Douwe B.; Kipping, Jens; Clausnitzer, Viola; Brunzel, Stefan; Brandl, Roland
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13134, in which Pinkert et al., study the drivers of cross‐taxon congruence, detect biodiversity refugia using climate diversity relationships and assess the coverage of biodiversity hotspots of sub‐Saharan Africa by protected areas.